Handbook of electrical and electronics technology - Johnson, Curtis D. (Prentice Hall, 1996)
This reference book is designed for practising professionals in electricity and electronics. It contains need-to-know information that is used everyday, for design, construction, testing and implementation. It should also be useful for students of electronics.